Evaluation of ascorbic acid impregnation by ultrasound-assisted osmotic dehydration in plantain - Martínez-Sánchez, C.E.; Solis-Ramos, Alma C.; Rodríguez-Miranda, Jesús; Juárez Barrientos, José Manuel; Ramírez-Rivera, Emmanuel J.; Ruiz-López, I. I.; Gómez-Aldapa, C.A.; Herman-Lara, Erasmo (Wiley-Blackwell, 2022)
The objective of this study was to evaluate the impregnation of ascorbic acid (AA) by ultrasound (US)-assisted osmotic dehydration (OD). A 25 factorial design was used. The highest water loss (WL) of 42% was obtained with the combined use of OD+US+AA. The effective diffusivities of water (EDw) and solids (EDs) were increased when OD was employed with a temperature of 60°C, a sucrose concentration of 60%, and a simultaneous application of US+AA treatments in plantain thin slices. The use of OD+US favored AA impregnation; in the treatment with 45% sucrose at 40°C, AA increased from 18% to 42%. Tonality did not change significantly in the OD+US+AA treatments at 40°C. However, except for the gumminess, significant differences from the control were observed in the texture profile analysis (TPA). In microstructure analyses, it was observed that by applying OD+US+AA, the cellular structure was not altered. Applying the specified operational conditions for OD, the AA impregnation pretreatments, and US, a plantain dry food could be obtained without reducing the specified quality parameters in this study.
Keywords: Ácido ascórbico